2007
DOI: 10.1111/j.1471-4159.2007.04654.x
|View full text |Cite
|
Sign up to set email alerts
|

Alanine metabolism, transport, and cycling in the brain

Abstract: Brain glutamate/glutamine cycling is incomplete without return of ammonia to glial cells. Previous studies suggest that alanine is an important carrier for ammonia transfer. In this study, we investigated alanine transport and metabolism in Guinea pig brain cortical tissue slices and prisms, in primary cultures of neurons and astrocytes, and in synaptosomes. Alanine uptake into astrocytes was largely mediated by system L isoform LAT2, whereas alanine uptake into neurons was mediated by Na(+)-dependent transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 63 publications
0
47
1
Order By: Relevance
“…This suggested that AMPA activation is specifically targeting a pool of lactate which is not rapidly accessible to 13 C from glucose. Evidence for such as pool has been presented previously [41] and our own experiments with [3-13 C]pyruvate as a substrate have indicated that more pools are labelled with this substrate than with [1-13 C]-glucose (e.g., [20,42,43]). …”
Section: Discussionmentioning
confidence: 75%
“…This suggested that AMPA activation is specifically targeting a pool of lactate which is not rapidly accessible to 13 C from glucose. Evidence for such as pool has been presented previously [41] and our own experiments with [3-13 C]pyruvate as a substrate have indicated that more pools are labelled with this substrate than with [1-13 C]-glucose (e.g., [20,42,43]). …”
Section: Discussionmentioning
confidence: 75%
“…Plasma alanine was considered to have minor contribution to brain metabolism since it exists at only 11.2 ± 3.2% of lactate concentration (quantified in PCA extracts of plasma samples by in vitro NMR spectroscopy). This is further supported by the relative low rate of alanine transport into the brain and contribution to metabolism (Bröer et al, 2007). …”
Section: Resultsmentioning
confidence: 87%
“…This decline and the associated decline in cortical alanine concentration contrast with an increase in the cortical concentration of both amino acids on the same day in control mice. The reciprocal changes in the cortical concentration of glutamine and alanine in GS-deficient and control neonates, which result in a 14-and 7-fold difference, respectively, indicate that the phenotype of GS deficiency in the brain emerges coincidentally with the developmental increase in the activity of the glutamineglutamate and the associated alanine-lactate cycles (Broer et al, 2007;Mackenzie and Erickson, 2004;Zwingmann and Leibfritz, 2003).…”
Section: Gs Excision Is Complete Well Before Functional Impairment Dementioning
confidence: 96%